(untitled) (Journal of the College of Basic Education, 2025)
The current study aimed to develop a visual stimuli device and examine its effect on improving passing and receiving skills in handball for fifth-grade students. The research problem arose from the researcher’s observation of a lack of device usage in teaching basic skills by physical education teachers.The significance of this study lies in assisting physical education teachers in utilizing this device as a supportive tool for learning and enhancing fundamental handball skills among school students. The researcher adopted an experimental approach using an equivalent groups design. The research population consisted of fifth-grade students from Al-Mustaqbal Primary School for the academic year 2024-2025, totaling 74 students. A random sample of 20 students was selected.Appropriate statistical methods (SPSS) were employed to analyze the results, which demonstrated a clear positive impact of the proposed device on the experimental group’s skill measurement and development. The study recommends focusing on teaching fundamental handball skills using available devices and tools.